A Human Paradox: The Nazi Legacy of Pernkopf’s Atlas - Hartsock, Jane A.; Beckman, Emily S. (Conatus - Journal of Philosophy, 2019)
Eduard Pernkopf’s Atlas of Topographical and Applied Human Anatomy is a four-volume anatomical atlas published between 1937 and 1963, and it is generally believed to be the most comprehensive, detailed, and accurate anatomy textbook ever created. However, a 1997 investigation into “Pernkopf’s Atlas,” raised troubling questions regarding the author’s connection to the Nazi regime and the still unresolved issue of whether its illustrations relied on Jewish or other political prisoners, including those executed in Nazi concentration camps. Following this investigation, the book was removed from both anatomy classrooms and library bookshelves. A debate has ensued over the book’s continued use, and justification for its use has focused on two issues: (1) there is no definitive proof the book includes illustrations of concentration camp prisoners or Jewish individuals in particular, and (2) there is no contemporary equivalent to this text. However, both points fail to address the central importance of the book, not simply as part of anatomy instruction, but also as a comprehensive historical narrative with important ethical implications. Having encountered a first edition copy, these authors were given a unique opportunity to engage with the text through the respective humanities lenses of history, ethics, and narrative. In doing so, an instructive and profound irony has surfaced: Nazis, including Pernkopf, viewed specific groups of people as less than human, giving rise to unthinkable atrocities perpetuated against them. However, these same individuals became the sources for the creation of the Atlas, which served as the model for primary instruction on the human form for more than half of the twentieth century. In this article, we recount the difficult and somewhat opaque provenance of this book, engage the ethical questions surrounding both its creation and its use, and ultimately propose a pedagogical methodology for its continued use in medical education.